DEVELOPMENT OF EVELOPMENT OF UKRAINIAN TAPESRY AS A COMPONENT OF DECORATIVE ART IN UKRAINE - Bashta, Olena Tryfonivna; Sydorova, Olena Ihorivna (Theory and practice of design, 2025)
Abstract. The article examines the development of Ukrainian tapestry from the late twentieth century to the early twenty-first century. The purpose of the study: to examine, compare and analyse the works of Ukrainian tapestry masters. Methodology. The main research methods chosen are the following: empirical, theoretical and empirical-theoretical. The empirical method includes observation, comparison, and generalisation. Theoretical methods include: ascent from the abstract to the concrete, abstraction, concretisation, identification and separation. Much of the work was carried out using empirical and theoretical methods, in particular, comparative analysis, induction, and deduction. Induction is cognition from facts to a certain hypothesis. Deduction is the movement of knowledge from the general to the particular and the derivation of consequences from premises. Results. On the one hand, the article examines aspects of the colour scheme of tapestries that emphasise the mood of the artists and the differences in techniques and methods, as well as materials favoured by tapestry masters. On the other hand, the identified features are common to a number of works, which are a manifestation of common trends in creativity. The transformation of images, change of colours, techniques and moods in the works of the masters from the 1970s to the first decades of the twenty-first century, when an active desire for plastic experiments and the search for new technological methods in the hand-weaving technique appeared in their work. Scientific novelty. The colors, techniques, and methods of the Ukrainian tapestry masters are studied. It was shown up that in comparison with the 1970s and 1980s, when the works of the masters were restrained, pastel, often black and white, in the 1990s and 2000s the color palette of the masters of artistic textiles changed to a bright, life-affirming one. The longed-for independence seemed to inspire the artists, filling their works with freedom, joy, and the desire for creative experiments. Practical relevance. The peculiarities of the color scheme of tapestries and techniques in the hand-weaving technique, revealed as a result of the study, can help tapestry masters and practicing designers expand the palette of creative possibilities in designing more colorful and emotionally rich residential and public interiors.